THE IMPACT OF REMOTE WORK ON THE IT COMPANIES, MADURAI (International Journal of Food and Nutritional Sciences, 2022)
Remote work means working from home with the use of ICT to coordinate and collaborate with the team. It has become a popular topic among all organizations, especially in the IT sector. With technology and internet availability on the rise, organizations across the globe have adopted these employee-friendly practices. The IT companies from Madurai are mostly outside the main city and the recent water crisis occurring in the region has forced the IT companies in this region to make use of remote working